THE ROLE OF MULTIMEDIA IN DEVELOPING GRAMMATICAL COMPETENCE IN ENGLISH IN GENERAL SECONDARY SCHOOLS (SCIENCE TIME JOURNAL, 2026)
The rapid integration of digital technologies into education has significantly transformed language teaching methodologies. In particular, multimedia tools have become an essential component in enhancing the effectiveness of foreign language instruction. This study explores the role of multimedia technologies in developing grammatical competence in English among students in general secondary schools. The research analyzes the pedagogical benefits of multimedia resources such as interactive presentations, educational videos, digital exercises, and language learning applications in grammar instruction. The study employs qualitative and theoretical analysis of modern teaching practices and examines how multimedia contributes to increasing learners’ motivation, improving comprehension, and facilitating the practical application of grammatical structures. The findings indicate that multimedia-based instruction enhances students’ grammatical accuracy, supports contextual learning, and promotes interactive classroom environments. Furthermore, multimedia resources enable teachers to present complex grammatical concepts in visually and auditorily engaging ways, thereby improving retention and understanding. The article concludes that the effective integration of multimedia technologies into English language teaching significantly contributes to the development of grammatical competence and recommends incorporating multimedia-based pedagogical strategies into secondary school curricula.